Boundary Value Analysis and Decision Table Testing Methods in Software Testing - Enjelina Sianturi (International Journal of Information Technology and Education, 2022)
Product quality is very important in the software development industry. The quality of the resulting product is strongly influenced by software testing before a software is deployed to customers. If a software has passed the test, it will be able to minimized the occurrence of obstacles when the software is used or operated. There are many software testing methods that can be used, from the black type to box testing and types of white box testing. in this study, a method of the black box testing type is used, namely boundary value analysis and decision table testing. The sample form being tested is part of the software used for the management of pension funds for a pension fund management institution employee. The sample form being tested is the periodic pension benefit claim submission form. then the test is carried out using the boundary value method analysis and decision table testing. Based on the business process rules of entry and form validation, a test scenario and data are created to be used for testing. After going through the testing process, the results showed that there were still things that needed to be improved on the sample form.